Prenatally Acquired Multiple Limb Ischemia in a Very Low Birth Weight Monochorionic Twin - Straňák, Zbyněk; Korček, Peter; Hympánová, Lucie; Kynčl, Martin; Krofta, Ladislav (Fetal diagnosis and therapy, 2017)
Limb ischemia is an extremely rare event occuring in monochorionic twin pregnancy complicated by twin-to-twin transfusion syndrome (TTTS) and twin anemia polycythemia sequence (TAPS). The authors describe a case of TTTS and TAPS treated successfully using amnioreduction and laser ablation. However, severe ischemia of both lower extremities in the recipient twin developed after the fetal treatment. This serious complication was diagnosed on MRI in utero and confirmed postnatally. Elective amputation of the affected limbs was performed. The etiology of the disease remains unclear despite profound clinical and histopathological examinations; although the role of thromboembolism in monochorionic pregnancy seems to be most likely, this unique case of multiple limb ischemia with distinct macroscopic findings has not yet been described.
Keywords: novorozenec s velmi nízkou porodní hmotností; dolní končetina; Pregnancy; Humans; fetofetální transfuze; Twins, Monozygotic; Ischemia; Female; dvojčata monozygotní; Amputation, Surgical; lidé; Twin-to-twin transfusion syndrome; Lower Extremity Deformities, Congenital; Infant, Very Low Birth Weight; Polycythemia; Lower Extremity; ženské pohlaví; vrozené deformity dolní končetiny; Fetofetal Transfusion; těhotenství; Monochorionic pregnancy; Anemia; ischemie; anemie; Multiple limb ischemia; amputace; polycytemie